Effect of Compositional and Processing Variations in New 5182-Type AlMgMn Alloys on Mechanical Properties and Deformation Surface Quality - Ebenberger, Paul (Materials (Basel), 2019)
Laboratory-scale sheets of 5182-type AlMgMn alloys with varying Mg and Mn contents and additions of different amounts of Zn, Cu, Zr and Er were studied. The sheets were produced using two different cold-rolling degrees and two soft-annealing treatment procedures: air-circulated furnace annealing at 370 °C with subsequent furnace cooling, and salt-bath annealing with subsequent water quenching. Mechanical properties and deformation surface quality were studied via tensile tests with simultaneous visual surface characterization. The influence of the chemical composition and the processing route on grain size, mechanical properties, and surface quality is discussed in the study. A reduction in the Mg content improves the surface quality after plastic deformation, but at the expense of the mechanical properties. The results suggest the presence of an optimum Mn content in terms of optical appearance and mechanical properties. Adding Zr largely inhibits recrystallization, which is reflected in a textured microstructure. Adding Er affects neither the surface quality nor the mechanical properties. Specific combinations of Zn or Cu addition, cold-rolling degree, and heat treatment generate significant improvements in the mechanical and optical properties. In general, annealing at high temperature with subsequent quenching leads to enhanced surface quality and mechanical properties, and adding Zn enables further noteworthy improvements.